Prevalence of childhood lead poisoning and respiratory disease associated with lead smelter emissions - Mark Patrick Taylor; Cynthia Faye Isley; John Glover (Environment International, 2019)
Background: The city of Port Pirie in South Australia has been a world leading centre for lead and zinc smelting and processing since 1889 that continues to cause contamination of its environment and resident population. This study quantifies the effect of lead and SO2 emissions from Nyrstar Port Pirie Pty Ltd's smelter on blood lead and respiratory health outcomes, respectively, and establishes what air quality values are required to better protect human health. Method: Blood lead and emergency department presentation data collected by South Australia Health (SA Health) and lead in air and SO2 data collected by the South Australian Environment Protection Authority (SAEPA) were obtained and analysed to quantify health outcomes due to smelter emissions in Port Pirie. Regression analysis was used to assess the relationship between the concentration of lead in air and children's blood lead levels between the years of available data: 2003 to 2017. Ambient SO2 concentrations (SAEPA) measured continuously between 2008 and 2018 were 24-hour averaged and compared to daily local emergency department respiratory presentation rates (available from July 2012 to October 2018). Rates of emergency department respiratory presentations at Port Pirie and regional comparators were calculated as age-standardised rates. Results: The data show that increases in ambient SO2 concentrations are associated with increased rates of emergency department respiratory presentations of Port Pirie residents, in which children are over-represented. The 30-day rolling average of respiratory presentations was significantly associated (p < 0.05) with incremental increases in SO2. Analysis of the relationship between lead in air and blood lead shows that annual geometric mean air lead concentrations need to be <0.11 μg/m3 to ensure the geometric mean blood lead of Port Pirie children under 5 years is ≤5 μg/dL. For children aged 24 months, lead in air needs to be no greater than 0.082 μg/m3 (annual geometric mean) to ensure geometric mean blood lead does not exceed 5 μg/dL. Conclusion: Current smelting emissions continue to pose a clear risk of harm to Port Pirie children. Allowable emissions must be lowered significantly to limit adverse childhood health outcomes including respiratory illness and IQ, academic achievement and socio-behavioural problems that are associated with lead exposure at levels experienced by Port Pirie children. Current SO2 levels are likely to be responsible for increased rates of emergency department respiratory presentations in Port Pirie compared with other South Australian locations. As a minimum, Australian SO2 air quality standards need to be enforced in Port Pirie to better protect human health. Lead in air needs to be approximately 80% lower than the current national standard (0.5 μg/m3) to ensure that the geometric blood lead of children under 5 years is less than or equal to 5 μg/dL. Keywords: Air quality, Children, Lead exposure, Sulfur dioxide (SO2), Respiratory disease